The Bank of Ghana's HIV/AIDS Education Program - Ruparel, Ravi (World Bank, Washington, DC, 2012)
This program was launched as part of a World Bank financed Financial Institutions project. When the project was extended for two years after June 2002, the World Bank encouraged project beneficiaries to develop a HIV/AIDS education program. Ghana's central bank, the Bank of Ghana (BOG), took up the challenge and implemented an intensive education program beginning April 2001. Although World Bank funding ceased in June 2002, BOG has continued the program as a wholly BOG-funded activity. The primary objective of the program was to prevent spread of infection among BOG staff by providing education that would lead to increased awareness of staff and their families about HIV/AIDS and eventually lead to positive behavior change. The program was implemented by a Secretariat of staff members from BOG's health clinic working under the guidance of a Supervisory Committee consisting of medical professionals and representatives of staff, management, and the government. The activities of the program included communication, condom distribution, voluntary testing, counseling, and treatment/care. Communication was done through seminars, lectures, drama and documentaries. The promotional materials used the "STOP AIDS LOVE LIFE" slogan which is the official slogan of the Government of Ghana's HIV/AIDS program. The program was designed to reach out to all of BOG's 2,600 staff and their 10,000 dependants across the country. BOG contracted an external firm to undertake a baseline survey which had 1178 respondents. A post-intervention survey undertaken in June 2002 had 852 respondents.